Business and Human Rights:a tense, mined and contested field - Oliveira, Cintia Rodrigues de; Alcadipani da Silveira, Rafael (Organizações & Sociedade, 2023)
The aim of this essay is to critically analyze the recent field of studies called Business and Human Rights, which addresses the negative impacts of human rights violations in the corporate sphere, housing theoretical discussions, principles, guidelines, regulations and regulations. We developed the essay by focusing on three central themes: the business activities of transnational corporations negatively impact human rights around the world; the initiatives created to address the impact of business on human rights are discursive and, therefore, far from practical; companies and corporations make use of various attempts to abstain from responsibility, even if they make symbolic and material reparations. For this, we illustrate with the abstention of corporate responsibility for human rights violations in the case of the murder of João Alberto de Freitas committed by Carrefour security guards in the parking lot of one of its stores in Porto Alegre, in the year 2020. Throughout the text, we argue that this field reveals the tensions between business and respect for human rights, understanding that it is a minefield and liable to be contested. Our contribution lies in pointing out ways for a more powerful involvement of researchers in the field of management, with the real problems that challenge societies, such as human rights violations within organizations.